Investigation of self-immolative linkers in the design of hydrogen peroxide activated metalloprotein inhibitors - Jourden, Jody L. Major; Daniel, Kevin B.; Cohen, Seth M. (Chemical communications (Cambridge, England), 2011)
A series of self-immolative boronic ester protected methyl salicylates and metal-binding groups with various linking strategies have been investigated for their use in the design of matrix metalloproteinase proinhibitors.